Experimental research on the longitudinal field generated by a tightly focused beam - 张明倩 王佳 田芊 (Chinese physics B, 2013)
The longitudinal optical field is a peculiar physical phenomenon that is always involved with the domain of near-field optics. Due to its extraordinary properties, it has recently attracted increasing attention in research and application. In this work, the longitudinal fields generated by the evanescent illumination of tightly focused, different polarized hollow beams are investigated. The focused light fields are numerically simulated according to vector diffraction theory, and their vector analysis is also carried out. The longitudinal fields on the focal plane are demonstrated experimentally using tip-enhanced scanning near-field microscopy. The simulation and experimental results show that the tightly focused radially polarized beam is suited to generating a stronger and purer longitudinal optical field at the focus.